2020
DOI: 10.1080/19475683.2020.1812716
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of spatiotemporal variability of water productivity in Ethiopian sugar estates: using open access remote sensing source

Abstract: spatiotemporal variability of water productivity in Ethiopian sugar estates: using open access remote sensing source, Annals of GIS,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
2
2
0
Order By: Relevance
“…This outcome indicates that the evaluation accuracy of the SPL3SMP_E soil moisture product aligns closely with its intended design accuracy. This finding is consistent with conclusions drawn from research conducted in other regions [49][50][51]. Simultaneously, the consistently negative values of MD may indicate a prevalent underestimation of soil moisture by the SPL3SMP_E soil moisture product in this specific region.…”
Section: Overall Accuracy Of the Spl3smp_e Soil Moisture Productsupporting
confidence: 91%
“…This outcome indicates that the evaluation accuracy of the SPL3SMP_E soil moisture product aligns closely with its intended design accuracy. This finding is consistent with conclusions drawn from research conducted in other regions [49][50][51]. Simultaneously, the consistently negative values of MD may indicate a prevalent underestimation of soil moisture by the SPL3SMP_E soil moisture product in this specific region.…”
Section: Overall Accuracy Of the Spl3smp_e Soil Moisture Productsupporting
confidence: 91%
“…The BWP of irrigated sugarcane in our study is comparable with the estimates of Gemechu et al (2020) who showed values ranging between 7.6 and 9 kg/m 3 in Wonji and 6.7 and 10 kg/m 3 in Metehara (Table 6). However, they show variations with the global WP ranges of sugarcane which range between ∼5 and 7 kg/m 3 in India and 3-6 kg/m 3 in Sao Paulo, Brazil due to the variations related to the soil type, sugar cane varieties, climate and management practices.…”
Section: Comparison Of Global Regional and Local Wpssupporting
confidence: 89%
“…In addition, crop models, hydrological models, remote sensing, statistics, and geographic information systems are usually used to analyze regional-scale water productivity [ 23 , 24 , 25 , 26 ]. Gemechu et al used remote sensing-derived datasets to map the seasonal and spatial variability of water productivity in sugarcane ( Saccharum officinarum L.) agriculture in three large irrigation schemes (Wonji, Fincha’a, and Metahara) in Ethiopia [ 27 ]. Ahmadpour et al proposed a joint estimation method of spatio-temporal variation of crop water productivity under a deficit irrigation scenario based on the AquaCrop model [ 28 ].…”
Section: Introductionmentioning
confidence: 99%